2020
DOI: 10.3390/en13164067
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Pore Structure of Tight Sandstone Based on Multifractal Analysis from NMR Measurement: A Case from the Lower Permian Taiyuan Formation in the Southern North China Basin

Abstract: Understanding the pore structure can help us acquire a deep insight into the fluid transport properties and storage capacity of tight sandstone reservoirs. In this work, a series of methods, including X-ray diffraction (XRD) analysis, casting thin sections, scanning electron microscope (SEM), nuclear magnetic resonance (NMR) experiment and multifractal theory were employed to investigate the pore structure and multifractal characteristics of tight sandstones from the Taiyuan Formation in the southern North Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…α min and α max are the minimum and maximum of the singularity exponent, respectively, and α 0 is the singularity exponent corresponding to the peak value of the singular spectrum; the smaller the value is, the greater the singular spectrum skews to the left, which indicates high heterogeneity. 49 α max − α min , α 0 − α max , and α min − α 0 represent the width of the whole, left branch, and right branch of the singular spectrum, respectively, and larger values of the parameters represent a more complex pore structure and higher pore heterogeneity. 50 Generalized fractal dimension spectrum parameters mainly included D min , D max , D 0 , D 1 , and D 2 .…”
Section: Raman Reflectancementioning
confidence: 99%
“…α min and α max are the minimum and maximum of the singularity exponent, respectively, and α 0 is the singularity exponent corresponding to the peak value of the singular spectrum; the smaller the value is, the greater the singular spectrum skews to the left, which indicates high heterogeneity. 49 α max − α min , α 0 − α max , and α min − α 0 represent the width of the whole, left branch, and right branch of the singular spectrum, respectively, and larger values of the parameters represent a more complex pore structure and higher pore heterogeneity. 50 Generalized fractal dimension spectrum parameters mainly included D min , D max , D 0 , D 1 , and D 2 .…”
Section: Raman Reflectancementioning
confidence: 99%
“…), and multifractal model. 26,27 Su et al 28 showed that single fractal dimensions D 1 and D 2 could represent the complexity of pore structures. Hao et al 29 showed a negative linear correlation between fractal dimension and porosity/permeability.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrate that NMR analysis provides key reservoir properties that can help with development and production decisions in unconventional reservoirs. 8 NMR has also been used to investigate pore structure in tight sandstones 10 and to obtain mobility of liquid hydrocarbons in well-characterized hierarchical carbon materials. 11 In addition, NMR has proved to be effective in studying bound water saturation and permeability in tight sandstones.…”
Section: Introductionmentioning
confidence: 99%